2020
DOI: 10.1080/0284186x.2020.1837947
|View full text |Cite
|
Sign up to set email alerts
|

Grade 2 acute GVHD is a factor of good prognosis in patients receiving peripheral blood stem cells haplo-transplant with post-transplant cyclophosphamide

Abstract: Guillaume (2020): Grade 2 acute GVHD is a factor of good prognosis in patients receiving peripheral blood stem cells haplo-transplant with post-transplant cyclophosphamide, Acta Oncologica,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Chronic GVHD showed a trend towards reduction of relapse but no effect on survival. Similarly, a French study showed improved outcome after haploidentical SCT with acute GVHD grade II [30]. The Baltimore group also reported similar observations with the use of PTCy after HLA-matched transplants [31].…”
Section: Discussionmentioning
confidence: 73%
“…Chronic GVHD showed a trend towards reduction of relapse but no effect on survival. Similarly, a French study showed improved outcome after haploidentical SCT with acute GVHD grade II [30]. The Baltimore group also reported similar observations with the use of PTCy after HLA-matched transplants [31].…”
Section: Discussionmentioning
confidence: 73%
“…The prevalence of grades III and IV GVHD can be greatly decreased with a PTCY-based GVHD prophylaxis. According to a recent retrospective research ( 74 ), the elderly patients’ survival outcomes benefit from the continuity of grade II aGVHD. Better DFS (HR: 0.36; p = 0.002) and OS (HR: 0.35; p = 0.003) for elderly patients with grade II aGVHD continue to show a substantial correlation, which may be attributable to controlled aGVHD and contributing to the GVL effect.…”
Section: Management Of Post-transplant Complicationsmentioning
confidence: 99%
“…Relapse in patients undergoing HSCT is strongly predicted by MRD positivity, BM CD34+ donor cell chimerism <80%, and persistent positivity for gene mutation or chromosomal gain or loss [74][75]. When the aforementioned risk factors appeared, we opted for preemptive treatment.…”
Section: Treatment Of Recurrence 721 Preemptive Treatment Of Recurrencementioning
confidence: 99%